Revolutionizing Vocabulary Learning: Enhancing English Mastery Through Kinetic Typography Art - Tuakia , Mohammad Daryono (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2022)
This study explores the potential of Kinetic Typography in enhancing vocabulary mastery in language learning. Traditional methods of vocabulary teaching can be ineffective due to their tedious nature. Kinetic Typography offers an engaging way of presenting vocabulary that can facilitate learners' understanding and retention. The study aims to design Kinetic Typography-based materials for vocabulary mastery and evaluate their effectiveness in improving the English vocabulary of seventh-grade students in Tangerang, Indonesia. The findings can contribute to the development of effective language learning materials that incorporate Kinetic Typography and advance research on its role in language learning. The methodology includes observation, interview, questionnaire, and vocabulary tests, with results analyzed using descriptive statistics. The effectiveness of the material will be evaluated by comparing mean scores of the vocabulary test before and after the treatment activity